The Effect of Kagan’s Structures on Divergent Thinking among Fourth-Grade Middle School Students in Biology - et. al., Hamid Tawfiq Hamid, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research aims to identify the effect of kagan structures on divergent thinking among fourth-grade middle school students in biology. The two researchers chose Al Zuhur Prep for Boys affiliated to the General Directorate of Education in Nineveh Governorate intentionally, division (A3) was chosen to represent the experimental group, and Division (B1) represented the control group, by (21) students per division, and the two researchers conducted parity between students of the two groups of research in The following variables: (previous biology information, divergent thinking (previous information), intelligence, previous achievement in biology), The two researchers identified the five chapters of the biology textbook for the fourth scientific grade and formulated the behavioral goals for the topics that he will study, so they were (157) behavioral goals in Bloom's six levels, and the researchers prepared a research tool, represented by the divergent thinking test. It may consist of six domains with two paragraphs for each field, and the following statistical methods were used: (the T-test for two independent samples, the Pearson correlation coefficient, and the equation (Cooper agreement, strength of distinction, Alpha - Cronbach, Aita square), in addition to the statistical bag of the social sciences. (Spss) and (Microsoft Excel)), and after analyzing the statistical results, it reached the superiority of the experimental group students in the divergent thinking test.